Cytomegalovirus-related Complications and Management in Facial Vascularized Composite Allotransplantation: An International Multicenter Retrospective Cohort Study. Issue 10 (6th April 2022) - Kauke-Navarro, Martin; Panayi, Adriana C.; Formica, Richard; Marty, Francisco; Parikh, Neil; Foroutanjazi, Sina; Safi, Ali-Farid; Mardini, Samir; Razonable, Raymund R.; Morelon, Emmanuel; Gelb, Bruce; Rodriguez, Eduardo; et al.
Abstract : Background: There is a paucity of data on the impact of cytomegalovirus (CMV) serostatus and CMV infection on outcomes in facial vascularized composite allotransplantation. Methods: This international, multicenter, retrospective cohort study presents data on CMV and basic transplant-related demographics, including pretransplant viral D/R serostatus, and duration of antiviral prophylaxis. CMV-related complications (viremia, disease), allograft-related complications (rejection episodes, loss), and mortality were analyzed. Results: We included 19 patients, 4 of whom received CMV high-risk transplants (D+/R−). CMV viremia was noted in 6 patients (all 4 D+/R− patients and 2 D−/R+), mostly within the first-year posttransplant, shortly after discontinuation of antiviral prophylaxis (median 2 mo). CMV disease occurred in 2 D+/R− patients. The high-risk group experienced relatively more rejection episodes per month follow-up. None of D+/R− patients suffered allograft loss due to rejection (longest follow-up: 121 mo). Conclusions: D+/R− patients were at increased risk of CMV-related complications. Although a higher number of rejections was noted in this group, none of the D+/R− patients lost their allograft or died because of CMV or rejection. Thus, CMV D+/R− face transplantation can likely be safely performed with prophylaxis, active surveillance, and prompt treatment. Abstract :